Complement Activation in Kidneys of Patients With COVID-19 - Pfister, Frederick; Vonbrunn, Eva; Ries, Tajana; Jäck, Hans-Martin; Überla, Klaus; Lochnit, Günter; Sheriff, Ahmed; Herrmann, Martin; Büttner-Herold, Maike; Amann, Kerstin; Daniel, Christoph (Frontiers in Immunology, 2021)
Most patients who became critically ill following infection with COVID-19 develop severe acute respiratory syndrome (SARS) attributed to a maladaptive or inadequate immune response. The complement system is an important component of the innate immune system that is involved in the opsonization of viruses but also in triggering further immune cell responses. Apart from the lung, the kidney is the second most common organ affected by COVID-19. Using immunohistochemistry for complement factors C1q, MASP-2, C3c and C5b9 we investigated the involvement of the complement system in 6 kidney biopsies with acute kidney failure in different clinical settings and three kidneys from autopsy material of patients with COVID-19. Renal tissue was analyzed for signs of renal injury by the detection of thrombus formation using CD61, endothelial cell rarefaction using ERG- and proliferation using PCNA-staining. SARS-CoV-2 was detected by in situ hybridization and immunohistochemistry. Biopsies from patients with hemolytic uremic syndrome (HUS, n=5), severe acute tubular injury (ATI, n=7) and zero-biopsies with disseminated intravascular coagulation (DIC, n=7) served as controls. Complement factor 3 was the dominant protein but collectin 11 and MASP2 were also identified in material clogging plasma adsorber used for extracorporeal therapy of patients with COVID-19. SARS-CoV-2 was sporadically present in varying numbers in some biopsies from patients with COVID-19. The highest frequency of CD61-positive platelets was found in peritubular capillaries and arteries of COVID-19 infected renal specimens as compared to all controls. Apart from COVID-19 specimens, MASP2 was detected in glomeruli with DIC and ATI. In contrast, the classical complement activation pathway (i.e. C1q) was hardly present in COVID-19 biopsies. C3c was strongly detected in renal arteries but also occurs in glomerular and peritubular capillaries of COVID-19 biopsies. Prominent C5b9 deposition as part of the complement terminal membrane attack complex was detected in COVID-19 biopsies predominantly in peritubular capillaries and renal arterioles with similar or even higher frequency compared to controls. In conclusion, various complement pathways were activated in COVID-19 kidneys and might be involved in the worsening of renal injury. Complement inhibition might thus be a promising treatment option to prevent deregulated activation and subsequent collateral tissue injury.